KAJIAN LAJU KOROSI TERHADAP STAINLESS STEEL DALAM LARUTAN HNO3 - Saloom Hilton Siahaan (LPPM Universitas Bina Bangsa, 2021)
This study aims to find out the rate of corrosion of stainless steel 304 in HNO3 solution. The dyeing process is carried out at a temperature of 700C for 6 hours, followed by a temperature of 290C for 18 hours every 7 days. This is to bring the use of stainless steel in real terms using SAMOP reactor tubes (Sub Critical Assembly for Mo99 Prad Action). Specimens undergoing TIG welding and electric arcs are cleaned of impurities, then measured, drawn, weighed, and recorded their initial weight. Furthermore, specimens are dyed in a solution of HNO3 pH 0.2 and 0.5 at a temperature of 700C for6 hours, continued at a temperature of 290C for18 hours every 7 days for 3 months. The heavy recording is done every week. The results showed weight loss in all specimens. This is seen at a pH corrosion rate of 0.5 in electric arc welding of 0.105 grams/dm2/month, for the rate of corrosion without welds is 0.026 grams/dm2/month. At pH 0.2 on electric arc welding is 0.045 grams/dm2/month at a pH of 0.2 without lashing 0.02 grams/dm2/month. Test objects that have undergone welding compared to test objects that do not experience welding occur significant corrosion rate differences.